当前位置:网站首页>[combinatorics] combinatorial identities (review of eight combinatorial identities | product of combinatorial identities 1 | proof | use scenario | general method for finding combinatorial numbers)
[combinatorics] combinatorial identities (review of eight combinatorial identities | product of combinatorial identities 1 | proof | use scenario | general method for finding combinatorial numbers)
2022-07-03 16:01:00 【Programmer community】
List of articles
- One 、 Review of combinatorial identities ( 8 individual )
- Two 、 Combinatorial identity ( product )
- 3、 ... and 、 Combinatorial identity ( product ) prove
- Four 、 Combinatorial identity ( product ) purpose 、 A general method for finding combinatorial numbers
Combinatorial identity reference blog :
- 【 Combinatorial mathematics 】 Combinatorial identity ( Recurrence Combinatorial identity | Change the next term to sum Combinatorial identity Simple and | Change the next term to sum Combinatorial identity Staggered and )
- 【 Combinatorial mathematics 】 Combinatorial identity ( Change the next term to sum 3 Combinatorial identity | Change the next term to sum 4 Combinatorial identity | binomial theorem + Derivation Prove the combinatorial identity | Use known combinatorial identities to prove combinatorial identities )
One 、 Review of combinatorial identities ( 8 individual )
1 . Combinatorial identity ( recursion ) :
( 1 ) recursion 1 :
(
n
k
)
=
(
n
n
−
k
)
\dbinom{n}{k} = \dbinom{n}{n-k}
(kn)=(n−kn)
( 2 ) recursion 2 :
(
n
k
)
=
n
k
(
n
−
1
k
−
1
)
\dbinom{n}{k} = \dfrac{n}{k} \dbinom{n - 1}{k - 1}
(kn)=kn(k−1n−1)
( 3 ) recursion 3 ( Pascal / Yang Hui's trigonometric formula ) :
(
n
k
)
=
(
n
−
1
k
)
+
(
n
−
1
k
−
1
)
\dbinom{n}{k} = \dbinom{n - 1}{k} + \dbinom{n - 1}{k - 1}
(kn)=(kn−1)+(k−1n−1)
2 . Review the combinatorial identities of summation under four variables : The combinatorial identity introduced earlier The number of combinations in
(
n
k
)
\dbinom{n}{k}
(kn) , Is the next item
k
k
k Have been accumulating changes , have
∑
k
=
0
n
\sum\limits_{k=0}^{n}
k=0∑n Cumulative property , Previous item
n
n
n It is the same. ;
( 1 ) Simple and :
∑
k
=
0
n
(
n
k
)
=
2
n
\sum\limits_{k=0}^{n}\dbinom{n}{k} = 2^n
k=0∑n(kn)=2n
( 2 ) Staggered and :
∑
k
=
0
n
(
−
1
)
k
(
n
k
)
=
0
\sum\limits_{k=0}^{n} (-1)^k \dbinom{n}{k} = 0
k=0∑n(−1)k(kn)=0
( 3 ) Change the next term to sum 3 :
∑
k
=
0
n
k
(
n
k
)
=
n
2
n
−
1
\sum\limits_{k=0}^{n} k \dbinom{n}{k} = n 2^{n-1}
k=0∑nk(kn)=n2n−1
( 4 ) Change the next term to sum 4 :
∑
k
=
0
n
k
2
(
n
k
)
=
n
(
n
+
1
)
2
n
−
2
\sum_{k=0}^{n} k^2 \dbinom{n}{k} = n ( n+1 ) 2^{n-2}
∑k=0nk2(kn)=n(n+1)2n−2
3 . Change the upper term to sum :
∑
l
=
0
n
(
l
k
)
=
(
n
+
1
k
+
1
)
\sum\limits_{l=0}^{n} \dbinom{l}{k} = \dbinom{n + 1}{k + 1}
l=0∑n(kl)=(k+1n+1)
Two 、 Combinatorial identity ( product )
Combinatorial identity ( product ) :
(
n
r
)
(
r
k
)
=
(
n
k
)
(
n
−
k
r
−
k
)
\dbinom{n}{r}\dbinom{r}{k} = \dbinom{n }{k}\dbinom{n-k}{r-k}
(rn)(kr)=(kn)(r−kn−k)
3、 ... and 、 Combinatorial identity ( product ) prove
1 .
(
n
r
)
(
r
k
)
\dbinom{n}{r}\dbinom{r}{k}
(rn)(kr) Combinatorial number analysis : This is the multiplication of two combinatorial numbers , It uses Step by step counting principle , Corresponding multiplication rule ;
( 1 ) First step :
(
n
r
)
\dbinom{n}{r}
(rn) from
n
n
n Of the elements
r
r
r Elements ;
( 2 ) The second step :
(
r
k
)
\dbinom{r}{k}
(kr) from
r
r
r Of the elements
k
k
k Elements ;
2 . The above choices may be repeated , The following counterexample can prove :
aggregate
S
=
{
a
,
b
,
c
,
d
,
e
}
S = \{ a, b, c, d, e \}
S={ a,b,c,d,e} , From this set
S
S
S Choose from
4
4
4 Elements , Two chestnuts :
①
{
a
,
b
,
c
,
d
}
\{a, b, c, d\}
{ a,b,c,d} , There are subsets
{
b
,
c
,
d
}
\{ b,c,d \}
{ b,c,d}
②
{
b
,
c
,
d
,
e
}
\{ b,c,d,e \}
{ b,c,d,e} , There are subsets
{
b
,
c
,
d
}
\{ b,c,d \}
{ b,c,d}
So from
5
5
5 Of the elements
4
4
4 individual , And then from
4
4
4 Of the elements
3
3
3 individual , Last There is a case of selecting duplicate subsets , There are two repetitions
{
b
,
c
,
d
}
\{ b,c,d \}
{ b,c,d} ;
3 .
(
n
k
)
(
n
−
k
r
−
k
)
\dbinom{n }{k}\dbinom{n-k}{r-k}
(kn)(r−kn−k) Combinatorial number analysis :
(
n
k
)
\dbinom{n }{k}
(kn) Express from
n
n
n Of the elements , Directly select
k
k
k Elements come out , See how many methods there are ; chestnuts : Above
5
5
5 Direct selection in meta set
3
3
3 Number of element subsets ;
(
n
−
k
r
−
k
)
\dbinom{n-k}{r-k}
(r−kn−k) yes The repeatability of the above selection method , How many times does each selection method appear ; chestnuts : Calculate each of the above
3
3
3 The number of repetitions of the element subset selection scheme ;
4 . Now let's start to study the above
(
n
−
k
r
−
k
)
\dbinom{n-k}{r-k}
(r−kn−k) How is the repeatability calculated
Take the chestnuts above for example ,
3
3
3 A subset of
{
b
,
c
,
d
}
\{ b,c,d \}
{ b,c,d} The reason why it happened twice is ,
stay
4
4
4 A subset of
{
a
,
b
,
c
,
d
}
\{a, b, c, d\}
{ a,b,c,d} and
{
b
,
c
,
d
,
e
}
\{ b,c,d,e \}
{ b,c,d,e} All contain the same
3
3
3 A subset of
{
b
,
c
,
d
}
\{ b,c,d \}
{ b,c,d} ,
In the above
4
4
4 Subsets , except
3
3
3 Outside the subset , There are other added elements ,
- stay
{
a
,
b
,
c
,
d
}
\{a, b, c, d\}
{ a,b,c,d} in , Added
a
a
a Elements
- stay
{
b
,
c
,
d
,
e
}
\{b,c,d,e\}
{ b,c,d,e} in , Added
e
e
e Elements
stay
3
3
3 Subsets , Add different elements , It can become Different
4
4
4 A subset of , Here we directly ask for
3
3
3 How many ways to add subsets , constitute
4
4
4 Number of subsets ;
The added element is from The original
S
=
{
a
,
b
,
c
,
d
,
e
}
S = \{ a, b, c, d, e \}
S={ a,b,c,d,e} Collection , Get rid of
{
b
,
c
,
d
}
\{ b,c,d \}
{ b,c,d}
3
3
3 Selected from the elements after the subset ,
The selected set has
5
−
3
=
2
5-3 = 2
5−3=2 Elements ( It's equivalent to a formula
n
−
k
n-k
n−k ) ,
The number selected is
4
−
3
=
1
4-3=1
4−3=1 individual ( It's equivalent to a formula
r
−
k
r-k
r−k ) ;
from
n
−
k
n-k
n−k Of the elements
r
−
k
r-k
r−k Elements , The number of programmes is
(
n
−
k
r
−
k
)
\dbinom{n-k}{r-k}
(r−kn−k) ;
5 .
(
n
r
)
(
r
k
)
=
(
n
k
)
(
n
−
k
r
−
k
)
\dbinom{n}{r}\dbinom{r}{k} = \dbinom{n }{k}\dbinom{n-k}{r-k}
(rn)(kr)=(kn)(r−kn−k) The left and right sides of are the counting results of the same combined number , So it's equal
Four 、 Combinatorial identity ( product ) purpose 、 A general method for finding combinatorial numbers
Combinatorial identity ( product ) :
(
n
r
)
(
r
k
)
=
(
n
k
)
(
n
−
k
r
−
k
)
\dbinom{n}{r}\dbinom{r}{k} = \dbinom{n }{k}\dbinom{n-k}{r-k}
(rn)(kr)=(kn)(r−kn−k)
encounter
(
n
r
)
(
r
k
)
\dbinom{n}{r}\dbinom{r}{k}
(rn)(kr) Product first , The case of re summation , If the sum is right
r
r
r Words of peace , namely
∑
r
=
0
n
\sum\limits_{r=0}^{n}
r=0∑n , as follows :
Yes
∑
r
=
k
n
(
n
r
)
(
r
k
)
\sum\limits_{r=k}^{n}\dbinom{n}{r}\dbinom{r}{k}
r=k∑n(rn)(kr) Sum up ;
Yes
r
r
r Sum up ,
r
r
r It's from
k
k
k Until
n
n
n ,
Previous items
(
n
r
)
\dbinom{n}{r}
(rn) Next is the variable ,
The following items
(
r
k
)
\dbinom{r}{k}
(kr) The last item is a variable ,
The previous general method : This makes it impossible to use the previous calculation method , The previous calculation method is , Constant to
∑
\sum
∑ Extract outside the symbol , The rest turns into Basic summation
∑
k
=
0
n
(
n
k
)
=
2
n
\sum\limits_{k=0}^{n}\dbinom{n}{k} = 2^n
k=0∑n(kn)=2n , Or known Combinatorial identity , Combination formula , To simplify ;
How to deal with the situation : Two combinatorial numbers , One is that the next item is the cumulative variable , One is that the previous term is an additive variable , Multiply two combinatorial numbers The situation of ;
Above The product combination identity can change the above situation into Next Is the case of cumulative variables ;
Use the above Product combinatorial identity , Turn into :
∑
r
=
k
n
(
n
r
)
(
r
k
)
=
∑
r
=
k
n
(
n
k
)
(
n
−
k
r
−
k
)
\sum\limits_{r=k}^{n}\dbinom{n}{r}\dbinom{r}{k} = \sum\limits_{r=k}^{n} \dbinom{n }{k}\dbinom{n-k}{r-k}
r=k∑n(rn)(kr)=r=k∑n(kn)(r−kn−k)
After obtaining the above formula , Items obtained by analysis
∑
r
=
k
n
(
n
k
)
(
n
−
k
r
−
k
)
\sum\limits_{r=k}^{n} \dbinom{n }{k}\dbinom{n-k}{r-k}
r=k∑n(kn)(r−kn−k) ,
Ahead
(
n
k
)
\dbinom{n }{k}
(kn) Item and Summation variables
r
r
r irrelevant ,
hinder
(
n
−
k
r
−
k
)
\dbinom{n-k}{r-k}
(r−kn−k) The next item is related to Summation variables
r
r
r relevant ;
therefore
(
n
k
)
\dbinom{n }{k}
(kn) term You can extract
∑
\sum
∑ Outside the symbol ;
=
(
n
k
)
∑
r
=
k
n
(
n
−
k
r
−
k
)
=\dbinom{n }{k} \sum\limits_{r=k}^{n} \dbinom{n-k}{r-k}
=(kn)r=k∑n(r−kn−k)
The above formula can be used Variable limit , Substitution calculation ; Use
r
′
=
r
−
k
r' = r-k
r′=r−k Replace
r
r
r ;
original
r
r
r The range of phi is zero
k
k
k ~
n
n
n , be
r
′
=
r
−
k
r' = r-k
r′=r−k The range of phi is zero
0
0
0 ~
n
−
k
n-k
n−k , The substitution result is as follows :
=
(
n
k
)
∑
r
′
=
0
n
−
k
(
n
−
k
r
′
)
=\dbinom{n }{k} \sum\limits_{r'=0}^{n - k} \dbinom{n-k}{r'}
=(kn)r′=0∑n−k(r′n−k)
according to Basic summation
∑
k
=
0
n
(
n
k
)
=
2
n
\sum\limits_{k=0}^{n}\dbinom{n}{k} = 2^n
k=0∑n(kn)=2n , Calculation
∑
r
′
=
0
n
−
k
(
n
−
k
r
′
)
\sum\limits_{r'=0}^{n - k} \dbinom{n-k}{r'}
r′=0∑n−k(r′n−k) As the result of the
2
n
−
k
2^{n-k}
2n−k ; The final calculation result is :
=
(
n
k
)
∑
r
′
=
0
n
−
k
(
n
−
k
r
′
)
=
2
n
−
k
(
n
k
)
=\dbinom{n }{k} \sum\limits_{r'=0}^{n - k} \dbinom{n-k}{r'} = 2 ^{n-k}\dbinom{n }{k}
=(kn)r′=0∑n−k(r′n−k)=2n−k(kn)
边栏推荐
- Second kill system 3 - list of items and item details
- [system safety] 43 PowerShell malicious code detection series (5) automatic extraction of ten thousand words from abstract syntax tree
- Microservice - Nacos registration center and configuration center
- 大csv拆分和合并
- [redis foundation] understand redis master-slave architecture, sentinel mode and cluster together (Demo detailed explanation)
- Redis在Windows以及Linux系统下的安装
- 近视:摘镜or配镜?这些问题必须先了解清楚
- 无心剑中译泰戈尔《漂鸟集(1~10)》
- Principles of several common IO models
- Download and install common programs using AUR
猜你喜欢
WinDbg analysis dump file
WinDbg分析dump文件
Three dimensional reconstruction of deep learning
"Remake Apple product UI with Android" (2) -- silky Appstore card transition animation
VS2017通过IP调试驱动(双机调试)
Vs2017 is driven by IP debugging (dual machine debugging)
Microservice - declarative interface call openfeign
App mobile terminal test [3] ADB command
[system safety] 43 PowerShell malicious code detection series (5) automatic extraction of ten thousand words from abstract syntax tree
远程文件包含实操
随机推荐
win32创建窗口及按钮(轻量级)
Microservice - declarative interface call openfeign
Popular understanding of ovo and ovr
Effect of ARP package on FTP dump under vxworks-6.6 system
Persisting in output requires continuous learning
Use percent sign in CString
pyinstaller不是内部或外部命令,也不是可运行的程序 或批处理文件
Detailed explanation of four modes of distributed transaction (Seata)
Create gradle project
Second kill system 3 - list of items and item details
Wechat payment -jsapi: code implementation (payment asynchronous callback, Chinese parameter solution)
《微服务设计》读书笔记(下)
Large CSV split and merge
【Proteus仿真】8×8LED点阵屏仿电梯数字滚动显示
【Proteus仿真】74HC595+74LS154驱动显示16X16点阵
Detailed pointer advanced 1
CString中使用百分号
Principles of several common IO models
"Remake Apple product UI with Android" (3) - elegant statistical chart
[combinatorics] combinatorial identities (sum of variable terms 3 combinatorial identities | sum of variable terms 4 combinatorial identities | binomial theorem + derivation to prove combinatorial ide